Bittersweet chocolate: the climate change impacts on cocoa production in Ghana - Bunn, Christian; Läderach, Peter R.D.; Quaye, Amos; Muilerman, Sander; Lundy, Mark M. (2015)
Climate change will be bittersweet for cocoa in Ghana. It will be less affected than other producer nations, but adaptation will be a tough challenge.